Study of the Mechanical and Morphology Properties of Recycled HDPE Composite Using Rice Husk Filler - Jia Ying Tong; Nishata Royan Rajendran Royan; Yong Chuen Ng; Mohd Hafizuddin Ab Ghani; Sahrim Ahmad (Advances in Materials Science and Engineering)
WPCs are being used in a large number of applications in the automotive, construction, electronic, and aerospace industries. There are an increasing number of research studies and developments in WPC technology involving rice husk as fillers. This study investigated the effects of different compositions of rice husk (RH) filler on the mechanical and morphological properties of recycled HDPE (rHDPE) composite. The composites were prepared with five different loading contents of RH fibers (0, 10, 20, 30, and 40 wt%) using the twin screw extrusion method. Maleic acid polyethylene (MAPE) was added as a coupling agent. Results showed that tensile and flexural properties improved with increasing RH loading. However, the impact strength of the composites decreased as the RH loading increased. SEM micrographs revealed good interfacial bonding between the fiber and polymer matrix.